Environmental injury to plants - American Chemical (Academic, 1990)
This book discusses several factors that contribute to plant stress, including: Freezing and chill injury, drought stress, heat shock, salt stress, toxic metals. The book alsso examines the detection of plant stress by remote sensing devices. The topics will be of interest to plant producers and will serve as a comprehensive overview of the recent trends in each of the specific stress categories. The work will also be invaluable to research investigating plant stress